Inter-test reproducibility of the lung clearance index measured by multiple breath washout. Issue 4 (5th October 2017) - Oude Engberink, Esther; Ratjen, Felix; Davis, Stephanie D.; Retsch-Bogart, George; Amin, Reshma; Stanojevic, Sanja
The lung clearance index (LCI) has strong intra-test repeatability; however, the inter-test reproducibility of the LCI is poorly defined. The aim of the present study was to define a physiologically meaningful change in LCI in preschool children, which discriminates changes associated with disease progression from biological variability. Repeated LCI measurements from a longitudinal cohort study of children with cystic fibrosis and age-matched controls were collected to define the inter-visit reproducibility of the LCI. Absolute change, the coefficient of variation, Bland–Altman limits of agreement, the coefficient of repeatability, intra-class correlation coefficient, and percentage changes were calculated. LCI measurements (n=505) from 71 healthy and 77 cystic fibrosis participants (aged 2.6–6 years) were analysed. LCI variability was proportional to its magnitude, such that reproducibility defined by absolute changes is biased. A physiologically relevant change for quarterly LCI measurements in health was defined as exceeding ±15%. In clinically stable cystic fibrosis participants, the threshold was higher (±25%); however, for measurements made 24 h apart, the threshold was similar to that observed in health (±17%). A percentage change in LCI greater than ±15% in preschool children can be considered physiologically relevant and greater than the biological variability of the test. Biological variability of lung clearance index is dependent on magnitude; % change is better for tracking patients http://ow.ly/tgbX30dBbCX